(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: The main question when comparing ESWL and PCNL for lower pole stones is one of clinical effectiveness, which includes consideration of the stone-free rate, secondary procedure rate, complications, hospitalization, disability period and recurrent stone rate. Many factors are contributed to lower pole stones clearance such as size of stone, composition, infundibulo-pelvic angle and patient clinical factors should all be considered in conjunction with the various surgical modalities and the availability of equipment’s before the preferred treatment option is selected. Stone-free rate with ESWL were inversely correlated to the stone burden treated. The introduction of ESWL in the early 1980s temporarily limited the indications for percutaneous procedures for stones but after limitations of shock wave lithotripsy were realized, percutaneous surgery regained its merited role in the stone management. On the other hand, lower pole stones contraindication for ESWL which were largely treated by open surgery in the past, now mostly replaced by PCNL. Objectives: To assess and compare relative efficacy and the overall lower calyceal stone clearance in between Percutaneous Nephrolithotomy (PCNL) and Extracorporeal Shock Wave Lithotripsy (ESWL). In relation to stone size. To compare the anatomical factor infundibulo-pelvic angle among, required adjuvant procedure and morbidity in between PCNL and ESWL in treating lower calyceal. Study Design: Hospital based prospective comparative interventional study. Setting: Study was carried out in the Department of urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), and different private hospital of Dhaka city, during the period of January 2006 to July 2007. Methods: Purposive sampling method was followed as per inclusion and exclusion by criteria to select 60 patients. They were divided into two groups by alternate method, into PCNL and ESWL groups. Result: In this study, for the smaller stones <10mm, it was seen that the rate of stone clearance in PCNL and ESWL group were 85.71% and 77.77% respectively. Statistical analysis shows no significant difference of stone clearance between the two groups. (P>0.05). For treating larger stones >10-20mm, present study showed that the rate of stone clearance in PCNL and ESWL group were 93.75% and 41.66 % respectively. There are statistical analysis shows significant difference of clearance (P<0.05). Conclusion: Percutaneous Nephrolithotomy (PCNL) is better option than Extracorporeal Shock Wave Lithotripsy (ESWL) in treating lower calyceal stone. J Com Med Col Teachers Asso July 2024; 28(2): 92-95